2006
DOI: 10.1557/proc-979-0979-hh11-18
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation Sequence in Mg-Zn-Sn Based Alloys

Abstract: Extensive experimental research work has been carried out in order to develop an Mg-Zn-Sn based creep resistant alloy. It was found that the addition of Y improves the structural stability of this alloy. The main goal of this work was to investigate precipitation sequence in Mg-Zn-Sn-Y alloys during aging at different temperatures. In order to elucidate the sequence of phase formation, XRD, TEM, SEM and EDS analyses were applied. It was found that, firstly, an hcp-MgZn2 phase nucleates homogeneously, and grows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…However, the effect of Sn on the precipitation behavior of the Mg-Zn system remains unclear. In addition, previous researches have shown that the Mg-Sn-Zn alloys are susceptible to rapid over-ageing [11]. Therefore, the microstructural charac- teristics and mechanical properties of a Mg-6Zn-3Sn-2Al alloy in the different states (F, T4 and T6) were studied in the present paper.…”
Section: Introductionmentioning
confidence: 98%
“…However, the effect of Sn on the precipitation behavior of the Mg-Zn system remains unclear. In addition, previous researches have shown that the Mg-Sn-Zn alloys are susceptible to rapid over-ageing [11]. Therefore, the microstructural charac- teristics and mechanical properties of a Mg-6Zn-3Sn-2Al alloy in the different states (F, T4 and T6) were studied in the present paper.…”
Section: Introductionmentioning
confidence: 98%